SOYBEAN ESTABLISHMENT AND SOIL PENETRATION RESISTANCE UNDER SOIL TILLAGE SYSTEMS AND SOWING SPEED IN TWO SEASONS - CORTEZ, JORGE WILSON; BONATO, MATHEUS DELABRIO; MARTINS, MURILO SOARES; GREITER, JOSÉ LUCAS GONÇALVES; ANGHINONI, MATHEUS (ENERGIA NA AGRICULTURA, 2021)
SOYBEAN ESTABLISHMENT AND SOIL PENETRATION RESISTANCE UNDER SOIL TILLAGE SYSTEMS AND SOWING SPEED IN TWO SEASONS JORGE WILSON CORTEZ¹, MATHEUS DELABRIO BONATO2, MURILO SOARES MARTINS3, JOSÉ LUCAS GONÇALVES GREITER4, MATHEUS ANGHINONI5 1 Eng. Agr., Prof. Dr. da Faculdade de Ciências Agrárias, Universidade Federal da Grande Dourados, Rodovia Dourados-Itahum, km 12, Cidade Universitária, 79804-970, Dourados, MS, Brasil, e-mail: jorgecortez@ufgd.edu.br . 2 Eng. Agr., Egresso da Faculdade de Ciências Agrárias, Universidade Federal da Grande Dourados, Rodovia Dourados-Itahum, km 12, Cidade Universitária, 79804-970, Dourados, MS, Brasil, e-mail: matheusbonato_@hotmail.com 3 Eng. Agr., Egresso da Faculdade de Ciências Agrárias, Universidade Federal da Grande Dourados, Rodovia Dourados-Itahum, km 12, Cidade Universitária, 79804-970, Dourados, MS, Brasil, e-mail: murilo_soares232@hotmail.com,. 4 Eng. Agr., Egresso da Faculdade de Ciências Agrárias, Universidade Federal da Grande Dourados, Rodovia Dourados-Itahum, km 12, Cidade Universitária, 79804-970, Dourados, MS, Brasil, e-mail: joselucas.greiter@gmail.com 5 Eng. Agr., Egresso da Faculdade de Ciências Agrárias, Universidade Federal da Grande Dourados, Rodovia Dourados-Itahum, km 12, Cidade Universitária, 79804-970, Dourados, MS, Brasil, e-mail matheus.anghinoni@gmail.com ABSTRACT: The objective was to evaluate the influence of soil management systems and sowing speed on the soil physical attributes of the soil and agronomic components of the soybean crop in two consecutive harvests. The trial was conducted in a randomized block design in a split plot scheme with four replications. In the plots, six management systems were applied: plowing at 0.40 m with moldboard plow, followed by two swivel levelling harrows, without soil mobilization, one chiseling at 0.35 m, two crossed chiseling at 0,35 m, one harrow - leveling and one chiseling harrow at 0.35 m and swivel leveling harrow. The sowing seeds were performed to each subplot, adding up four speeds in the 2014/2015 crop season and three in the 2015/2016 crop season. To evaluate the trial were recorded the data about, the percentage of soil coverage, resistance to penetration, number of days to emergency, stand and longitudinal distribution. The data was subjected to analysis of variance and test of means. The results showed that non-soil mobilization did not show an increase in soil compaction. The soil cover decreased the resistance to penetration. A less soil mobilization, showed a rapid seedling emergency. An increased on sowing speed increased the percentage of failure spacing decreasing sowing quality . Keywords: mechanization, no-tillage, soil compaction, Glycine max. ESTABELECIMENTO DA SOJA E RESISTÊNCIA À PENETRAÇÃO DO SOLO EM SISTEMAS DE MANEJO E VELOCIDADES DE SEMEADURA EM DUAS SAFRAS RESUMO: Objetivou-se avaliar a influência dos sistemas de manejo do solo e da velocidade de semeadura nos atributos físicos do solo e componentes agronômicos da cultura da soja em duas safras consecutivas. O ensaio foi conduzido no delineamento em blocos ao acaso no esquema de parcela subdividida com quatro repetições. Nas parcelas, foram aplicados seis sistemas de manejo: aração a 0,40 m com arado de aivecas, seguido de duas gradagens destorroadora - niveladoras, gradagem destorroadora - niveladora, sem mobilização, escarificador a 0,35 m uma única vez, escarificador a 0,35 m duas vezes cruzado, mais uma gradagem destorroadora - niveladora e escarificado a 0,35 m mais gradagem destorroadora - niveladora. Em cada subparcela foram alocadas as velocidades de semeadura, quatro velocidades na safra 2014/2015 e três na safra 2015/2016. Foi avaliada a porcentagem de cobertura do solo, a resistência à penetração, número de dias para emergência, estande e distribuição longitudinal. Os dados foram submetidos a análise de variância e teste de médias. Quando não ocorre mobilização/preparo do solo tem-se aumento da compactação do solo. A cobertura do solo diminuiu a resistência a penetração. Quanto menor a mobilização/preparo do solo mais rápido é a emergência das plântulas. Increased travel speed increased the percentage of flawed spacing diminuindo a qualidade da semeadura. Palavras-chaves: mecanização, plantio direto, compactação, Glycine max.